PENGEMBANGAN ORGANISASI MELALUI TEAM BUILDING, KOMPETISI DAN KERJASAMA - Fachry Fachry (Nurul Jadid University, 2015)
To develop an organization basically is not an easy matter, because to do development there must be some things that change. Though not everyone likes change, so it is not rare to find an emotional reaction to the emergence of either rational or irrational from various parties at the time of the change. This often happens because they do not think beyond what has been achieved with what was supposed to be generated in a state that is not too different. And if they can form a team performance in the organization he leads, then any problems faced by the organization will be more easily overcome. In addition, the productivity will increase the team's performance, the time could be used more effectively, and the cost can be reduced expenditures. Competition occurs in the body of an organization (internal competition) on the one hand it is very prone to cause friction or conflict between members in it. However, it does not mean that the competition should be avoided but that must be done is to manage these conditions are good for the interests and progress of the organization in the future. With the creation of the competitive climate in the organization, each individual and work unit will try to show the best performance of self and the group.